Strategic Delegation and Delay in Negotiations over the Bargaining Agenda - Conlin, Michael; Furusawa, Taiji (Journal of Labor Economics, 2000)
This paper develops a game‐theoretic model that endogenizes the items included in the bargaining agenda. The model's equilibria suggest two possible sources of inefficiency: (1) exclusion of items from the bargaining agenda and (2) delay to agreement due to negotiations over the bargaining agenda. Evidence from union contract negotiations is provided to demonstrate the relevance of these sources of inefficiency. The model also allows strategic delegation by the union. In certain equilibria, the surplus‐maximizing union selects wage‐maximizing delegates (such as senior union members) to negotiate the contract.